The Effect of Interval Training on Lung Vital Capacity of Futsal Athletes State High School 1 Toili Banggai Regency - Onan Christanto Sepang; Bambang Budi Rahardjo; Sulaiman Sulaiman; Sri Sumartiningsih (Journal of Physical Education and Sports, 2022)
This study aims to observe, analyze, and increase the vital capacity of futsal athletes using the interval training method, a quantitative type of research with pretest and posttest approach models. The sample in this study was 12 futsal athletes from Senior High School 1 Toili Banggai Regency. The study was conducted by giving the model interval training for 16 training meetings and then measuring it using a spirometry type SP70B with a unit of measurement in liters (L). The training is carried out with a training program with a 20-meter trajectory with repetitions and improvements given in stages. The data were analyzed using the normality test followed by the T-test to see the increase and significance that occurred using SPSS version 26.00. The results showed an increase in the vital capacity of the athletes' lungs after carrying out the exercise. Pretest results were 3.0600 ± 0.2340 and posttest results were 3.3617 ± 0.2744. Athletes experienced an average increase of 0.3016 while for a significance result of 0.000 <0.05, there is an increase in effect. Interval training can increase lung vital capacity for futsal athletes at Senior High School 1 Toili Banggai Regency